122 The efficacy of extended-release eprinomectin for the reduction of horn flies, face flies, and fecal egg counts of parasitic nematodes in replacement beef heifers. (29th July 2019) - Landers, Sophia F; Tucker, Christopher; Powell, Jeremy G; Wray, Eva; Cauble, Reagan; Lester, Toby D
Abstract: The purpose of this study was to evaluate the efficacy of extended-release eprinomectin against horn flies, face flies, and fecal egg counts of parasitic nematodes in crossbreed replacement beef heifers. Fifty-four heifers were randomly placed into three treatment groups (n = 18 heifers/treatment). Group 1 was administered the labeled dosage of extended-release eprinomectin at the onset of fly season (day 0). Group 2 acted as the negative control. Group 3 received the anthelmintic injection once a quarter of the heifers in the group reached the threshold treatment level for horn flies (n = 200 flies/animal; day 41). All cattle were separately pastured for the duration of the study. Throughout the study, nematode infections were measured via fecal egg counts while horn and face flies were visually monitored. Evaluation of pregnancy status was recorded at the conclusion of the study (day 144). Due to the high number of face flies, heifers were treated with insecticide dusts twice during the study (day 54 and 69). Group 1 averaged a fecal egg count of (2.3), group 2 (7.4), and group 3 (9.1) (day 111). Low egg counts for all treatment groups reflected minimal parasite burden which likely had little effect on treatment groups. Extended release eprinomectin had little influence on face flies given that all groups were above threshold at days 40, 48, and 54. At study conclusion, horn fly population was lower (P < 0.05) for group 1 (405.6) compared to group 2 (680.6) and group 3 (680.6). Conception rates were greater (P < 0.05) in group 1 (89%) compared to the control heifers (56%) and group 3 exhibited an intermediate rate (72%). Results indicate that although treatment with extended-release eprinomectin did not decrease the face fly burdens, it did have an effect on fecal egg counts, horn fly burdens, and subsequent pregnancy status at the conclusion of the study